Brief imagery rescripting vs. Usual care and treatment advice in refugees with posttraumatic stress disorder: a multi-center randomized controlled clinical trial - Steil, Regina; Ehring, Thomas; Nater-Mewes, Ricarda; Rüger, Mirjam Sophie; Weise, Cornelia; Morina, Nexhmedin (55th EABCT Congress 2025, 2025)
Background: Numerous refugees have undergone various traumatic experiences in their home countries and/or during their journey to safety. Within this population, trauma-related disorders like posttraumatic stress disorder (PTSD) or complex PTSD (CPTSD) are widespread, underscoring the urgency for accessible and impactful treatment. Imagery Rescripting (ImRs), an innovative treatment for PTSD that relies on imagery without formal exposure, has garnered increasing attention and shows promise as a potential approach. Objective: In this multi-center randomized-controlled trial, the objective is to explore the effectiveness of ImRs for refugees in comparison to Usual Care and Treatment Advice (UC+TA) concerning the remission of PTSD and the alleviation of other associated symptoms. Method: We randomized 94 refugees with a diagnosis of PTSD according to DSM-5. Forty-eight patients were randomized to the ImRs group. These patients received ten to twelve sessions of ImRs. Assessments were carried out at baseline, post-intervention, three-month follow-up, and 12-month follow-up. The primary outcome was the PTSD remission rate. Secondary outcomes included the severity of PTSD and CPTSD symptoms, psychiatric and dissociative symptoms, sleep quality and treatment satisfaction. Results: Remission from PTSD-DSM-5 differed significantly between the two groups at the 12-months follow-up. However, women were more often in remission than men. The symptom-severity was significantly lower for the ImRs group at the 12-month follow-up. There were significant improvements in the ImRs group as compared to the UC+TA group regarding self-reported PTSD-symptoms at the post and 12-month follow-up assessment, respectively. Self-reported comorbid symptoms were significantly improved in the ImRs group at post-assessment. Conclusions: Recent findings indicate the suitabilty of ImRs in addressing PTSD among refugees. Findings of this study support this assumption but indicate that women benefit more than men, which is in line with previous meta-analyses on PTSD-treatments. Additional treatment components, e.g. social work would be necessary to effectively address the complex situation of refugees in Germany and PTSD-treatments that are effective for men should be developed.